System identification and analysis of a non-isothermal CSTR for control purposes - Quitain, Armando Tibigin (Animo Repository, 1996)
The non-isothermal Continuous-Stirred Tank Reactor (CSTR) system is identified experimentally making use of least squares method. Mathematical models such as difference equation, differential equation and transfer function showing the effect of water flowrate and reactants' concentration hydrogen peroxide and sodium thiosulfate (H2O2 and Na2S2O3) on reactor temperature are developed. Based on the developed models, parameters of commonly used feedback controllers are evaluated using the recommended Ziegler-Nichols controller settings. Stability of the control system is also analyzed using the Bode Stability criterion. Results shows that the order of the linear differential equations defining the effect of the variables method above on reactor temperature does not exceed two (2). While Proportional-Integral-Derivative (PID) mode best controls the CSTR at a predefined setpoint, P mode is sufficient to control it using Na2S2O3 concentration as manipulated variable. Further, Ziegler-Nichols controller settings fail for PI mode of control.